Analisis structural equation modeling (SEM) pengaruh kepercayaan, persepsi kemudahan penggunaan, persepsi manfaat, persepsi resiko dan keinginan membeli online pada anggota forum jual beli kaskus.us.: (studi kasus: FJB kaskus.us) - Ardikoesoema, Nurmansyah (Institute for Advanced Science Social, and Sustainable Future, 2024)
This research uses structural equation models (SEM) as a theoretical basis for assessing Kaskus.us members' perceptions of ease of use and perceived benefits, which are strengthened by external factors, namely trust. The research population is all Kaskus.us members who have posted any information on the Kaskus.us Buying and Selling Forum. The researchers used purposive sampling and convenience sampling methods in this study. We also utilized structural equation modeling (SEM) analysis. The research found that as many as 200 people surveyed stated that trust had a significant influence on their intention to buy goods online on the Kaskus.us Buying and Selling Forum. In addition, research findings show that ease of use and benefits also have a significant influence on the intention to purchase goods online. The main objective of this research is to analyse the influence of perceived ease of use, perceived usefulness, and trust of Kaskus.us members on their intention to make online purchases. This research involved 200 respondents who were active members of the Kaskus.us Buying and Selling Forum and used structural equation modelling (SEM) nalysis. The results show that platform trust, ease of use, and perceived usefulness significantly influence respondents' desire to make online purchases through the platform.